The wolf from the Middle Pleistocene site of Ostiense (Rome). The last occurrence of Canis mosbachensis (Canidae, Mammalia) in Italy - Mecozzi, Beniamino; Iurino, Dawid A.; Profico, Antonio; Rosa, Carlo; Sardella, Raffaele (Historical Biology, 2020)
The phyletic relationship between Canis lupus and the Early-Middle Pleistocene Canis mosbachensis is widely accepted among scholars, although the taxonomy of several European fossil specimens is still debated. In the last decades, many studies focused on the evolution of Pleistocene wolves have been proposed considering new materials as well as specimens belonging to historical collections. The canid remains recovered during the last century and housed in museums, undoubtedly represent a valuable source of biometric and morphological data which require, in some cases, an updated review of the fossil material. Indeed, cases of stratigraphic and taxonomic misinterpretations represent a potential loss of information for understanding the palaeobiology of these iconic predators. Here we provide the first updated description of the specimen belonging to the collection of the Italian geologist and palaeontologist Alessandro Portis dating back to the early last century. Previously reported as Canis lupus, the cranium from the historical excavation of Ostiense palaeontological site (Rome, Italy) is ascribed to the Early-Middle Pleistocene wolf Canis mosbachensis. Moreover, the reassessment of the stratigraphic and geological data of the Ostiense site led to consider the studied specimen as the last occurrence of the Mosbach wolf in the Italian fossil record.